The organizational response to social problems - Schutt, Russell K.; Hartwell, Stephanie W. (Research in social problems and public policy, 2001)
From the de-institutionalization of psychiatric hospitals to the privatization of prisons, the dramatic public policy changes of the last three decades have been, to a large extent, changes in organization. The chapters in this volume examine these organizational changes. We learn how organizations shift strategies, create alliances, cross boundaries and react to incentives as they respond to changing environmental pressures. We learn about the complex relationships between organizations and their clients and how these relations can be altered in response to environmental change. Chapters in the first section focus primarily on inter-organizational relations among health care and community development organizations. Chapters in the second section focus primarily on relations between organizations and their clients, both in medical organizations and in the criminal justice system.